EFISIENSI TEKNIS DAN PENDAPATAN USAHA TANI BAWANG MERAH DI KECAMATAN KOTA GAJAH KABUPATEN LAMPUNG TENGAH - Adam Rahmatulloh; Fembriarti Erry Prasmatiwi; Lina Marlina (Lampung University, 2021)
This study mainly purposes to analyze revenue, risk, relationship between revenue with risk, technical efficiency, and factors that affecting technical efficiency of shallot farming. The research location is located in Kota Gajah Sub District, Central Lampung Regency with and the data was collected in July - August 2019 using census method. The number of respondents are 40 farmers members of three farmer groups who have planted shallots. The data are analyzed using revenue analysis, coefficient of variaton, Pearson Correlation Analysis, technical efficiency using Frontier Function, and multiple linear regression. The study shows that shallot farming income from cash costs and total costs Rp15.142.901,83/hectare and Rp4.002.020,84/hectare, respectively. Therefore coefficient of variation of income risk is 1,02 indicating that the risk of farming is very high. The relationship between revenue risk and revenue level is quite close. The shallot farming is technically efficient yet. The factors that significantly affecting technical efficiency are farming costs, revenue, and revenue risk.Key words: efficiency, farmers, revenue, risk, shallot.